Particle emissions and respiratory exposure to hazardous chemical substances associated with binder jetting additive manufacturing utilizing poly methyl methacrylate - Van Der Walt, Sylvia; Du Preez, Sonette; Du Plessis, Johannes L (Hygiene and Environmental Health Advances (Online), 2022)
•Binder jetting additive manufacturing involves different levels of inhalation risks•Respiratory exposure to PMMA has been linked to acute adverse health effects•Powders used for additive manufacturing are often recycled•Personal exposure monitoring results indicated inhalable particles•Additive manufacturing facilities should conduct physical and chemical characterisation analyses for the feedstock powders•Information and training are important for additive manufacturing operators During industrial scale binder jetting utilising poly methyl methacrylate (PMMA) hazardous chemical substances (HCSs) such as PMMA powder particles, methyl methacrylate (MMA) and acetone may be emitted and potentially inhaled by Additive Manufacturing (AM) operators. Physical and chemical characterisation of virgin and used PMMA powder samples were characterised in terms of their size, shape and chemical composition. Direct reading particle counting instruments were used to determine particle emissions and emission rates (ER). Internationally recognised methods were used to monitor HCSs in the ambient workplace environment and personal respiratory exposure of the AM operators. There were no differences between the median powder size distributions of virgin and used PMMA powders. Scanning Electron Microscopy images indicated the presence of <10 µm and <4 µm sized particles in virgin and used powders. Particle ERs as high as 3.33 × 106 particles/min for 0.01 - ∼1.00 µm sized particles were measured during the post-processing phase. Inhalable and respirable particles, acetone, pentane and toluene were detected in ambient air and AM operators were exposed to quantifiable concentrations of these HCSs. Particles sized 0.01 - ∼1.00 µm were the most prevalent particles emitted, with a maximum ER of 3.33×106 particles/min. Eight-hour Time Weighted Average personal exposures were below their respective Occupational Exposure Limit (OELs), with the exception of inhalable particles (mean >50% of the South African OEL). Recommendations were made to reduce exposure to inhalable particles, which could be applied to other AM facilities.